Hedge funds, CDOs and the financial crisis: An empirical investigation of the “Magnetar trade” - Mählmann, Thomas (Journal of Banking & Finance, 2013)
The so called Magnetar trade (a kind of capital structure arbitrage on the US housing market, using CDS and synthetic CDOs, and exploiting rating-dependent mispricing of risk) has gained a high publicity due to a Pulitzer Prize awarded media story from two journalists of ProPublica (an online news outlet). The story essentially claimed that the mortgage investment strategy of the hedge fund Magnetar during the period between 2006 and mid 2007 was based on a desire to construct CDO deals with riskier assets so that they could place bets that portions of their own deals would fail. This paper provides several pieces of evidence in line with the argument that tranches from Magnetar-sponsored CDOs present overly risky investments. However, investors and rating agencies appear to have adjusted their required spread levels and ratings to reflect this higher riskiness, at least to some extent.